The Development of Smart Armband with Emergency Button for Healthcare - Nor Amira Husna Mohd Akhir; Ts. Dr. Mohd Hezri bin Mohd Lwi @ Mokhtar (Progress in Engineering Application and Technology, 2024)
The project provides a real-time health monitoring service to address the difficulties faced by people managing chronic diseases. For those with chronic conditions, keeping track of their health and managing complicated medication regimens might be too much to handle. This can result in missed visits, ignored prescriptions, and dire repercussions. Monitoring the health of people with impairments or chronic illnesses presents additional obstacles for caregivers and healthcare professionals, particularly when it comes to the elderly. Designing a software-based pulse rate monitoring application, putting in place an armband for tracking emergencies and detecting pulse rates, and fusing emergency alert features in mobile apps are some of the goals. The smart armband that was designed effectively tracks the pulse rate of patients, takes care of caregivers real-time for patients and also used as an emergency tracker. Including emergency notification and medical functions in one smart armband is a great way to help people with chronic diseases such as heart disease manage their health and well-being. It provides a thorough and easy-to-use method of managing healthcare